Trade reforms, market access and poverty in Argentina - Porto, Guido Gustavo (2003)
This paper examines the impact of national and foreign trade reforms on poverty in Argentina. National reforms include the removal of Argentine import tariffs. Foreign reforms include the elimination of agricultural subsidies, and tariffs and non-tariff barriers in developed countries (i.e. the United States and the European Union). From a head count ratio of 25.7 percent in 1999, a combination of domestic and global trade liberalization would cause a decline of between 1.6 and 4.6 percentage points in the poverty rate. The marginal effects of national trade reforms are larger than those of foreign trade reforms. However, there is a much greater scope for policy reforms in developed countries. In Argentina, in the end, I find that foreign reforms are more important than national reforms in terms of poverty alleviation.